Perlawanan Terhadap Genosida: Analisis Dampak Fatwa MUI Tentang Boikot Perusahaan Terafiliasi Israel - Makrufah, Amirotul; Fahrurrozi, Fahrurrozi (Islamika : Jurnal Ilmu-Ilmu Keislaman, 2024)
The Palestinian-Israeli conflict has been raging for decades, triggering a global response including a boycott of products affiliated with Israel. The issuance of MUI fatwa number 83 of 2023 encouraged the Muslim community to support the Palestinian cause through boycott actions to suppress the economic power of pro-Israel companies. This study aims to analyze the impact of the MUI fatwa on the revenue of companies affiliated with Israel and understand the motivation and impact of changes in consumer consumption behavior that follow the boycott. The analysis was conducted by combining interview results and financial statement data to provide a comprehensive picture. The results show that religious, moral and social factors make consumers participate in boycotting products affiliated with Israel. This change in consumer consumption behavior is reflected in the financial statement data of PT Mitra Adiperkasa Tbk, which experienced a decrease in revenue from Rp 1.489 trillion to Rp 413.991 billion after the MUI fatwa number 83 of 2023. This shows that MUI's fatwa is able to become a moral guideline for consumers to support Palestine by suppressing the economic power of companies affiliated with Israel. This research provides insight into the influence of sharia fatwa on consumer behavior and its impact on company revenue.